METODE GASING SEBAGAI STRATEGI EFEKTIF PERKALIAN DUA DIGIT BAGI SISWA SMPK ADISUCIPTO - Luon, Maria Adriani Pulo; Leton, Samuel Igo; Henidin, Theresia (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
Two digit multiplication ability is an essential numeracy skill for junior high school students as a foundation for understanding more advanced mathematical topics such as linear equations, ratios, and algebra. However, observations at SMPK Adisucipto, particularly in class VII D, indicate that many students still experience difficulties performing two-digit multiplication quickly and accurately. This study aims to analyze the effectiveness of the Gasing method (Easy, Fun, and Enjoyable) in improving two digit multiplication skills among 31 seventh-grade students at SMPK Adisucipto. The research employed a one-group pretest–posttest design. The instruments included a two-digit multiplication test and a student learning activity observation sheet. The results showed a significant increase in students’ average scores, from 56.80 on the pretest to 85.40 on the posttest. Student responses toward the Gasing method were also highly positive, with percentages ranging from 85% to 95% in the categories of effectiveness, ease, speed, and simplicity. These findings demonstrate that the Gasing method not only improves learning outcomes but also creates a simpler, more enjoyable, and more meaningful learning experience ABSTRAK Kemampuan perkalian dua digit merupakan keterampilan numerasi yang penting bagi siswa SMP sebagai dasar untuk memahami materi lanjutan seperti persamaan linear, perbandingan, dan aljabar. Namun, hasil observasi di SMPK Adisucipto, khususnya pada kelas VII D, menunjukkan bahwa banyak siswa masih mengalami kesulitan dalam melakukan perkalian dua digit secara cepat dan tepat. Penelitian ini bertujuan menganalisis efektivitas metode Gasing (Gampang, Asyik, dan Menyenangkan) dalam meningkatkan kemampuan perkalian dua digit pada 31 siswa kelas VII D SMPK Adisucipto. Pendekatan penelitian menggunakan desain pretest-posttest one group design. Instrumen penelitian berupa tes kemampuan perkalian dua digit dan lembar observasi aktivitas belajar. Hasil penelitian menunjukkan peningkatan yang signifikan pada nilai rata-rata siswa dari 56,80 pada pretest menjadi 85,40 pada posttest. Respon siswa terhadap metode Gasing juga sangat positif dengan persentase 85–95% pada kategori efektivitas, kemudahan, kecepatan, dan kesederhanaan. Temuan ini menunjukkan bahwa metode Gasing tidak hanya meningkatkan hasil belajar, tetapi juga menciptakan pengalaman belajar yang lebih sederhana, menyenangkan, dan bermakna.